2000
DOI: 10.2190/vvpv-p3pf-j346-nr7t
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Death Anxiety and Denial in Death-Risk and Death-Exposure Occupations

Abstract: This study investigates the relationship between death anxiety and denial scale scores of persons employed in death-risk (DRG), death-exposure (DEG), or low-risk (CG) occupations. Participants were active duty military (DRG), health care providers (DEG), and college students (CG). Death anxiety instruments selected were Hoelter's Multidimensional Fear of Death Scale (MFODS) and Templer's Death Anxiety Scale (DAS). Spielberger's Rationality/Emotional Defensiveness (R/ED) Scale was the denial measure. The two de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
9
1
Order By: Relevance
“…Participants who had lower levels of death anxiety did not appear to invoke denial as a coping mechanism against the fear of death. This finding is contrary to the findings of Lewis, Espe-Pfeifer, andBlair (1999-2000) and Fleischmann (2002Fleischmann ( -2003 who found that individuals in high death exposure occupations who had low measures of death anxiety did, in fact, report the presence of a denial construct. In the current study, denial did correlate positively with intrinsic religiosity.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Participants who had lower levels of death anxiety did not appear to invoke denial as a coping mechanism against the fear of death. This finding is contrary to the findings of Lewis, Espe-Pfeifer, andBlair (1999-2000) and Fleischmann (2002Fleischmann ( -2003 who found that individuals in high death exposure occupations who had low measures of death anxiety did, in fact, report the presence of a denial construct. In the current study, denial did correlate positively with intrinsic religiosity.…”
Section: Discussioncontrasting
confidence: 72%
“…The challenge is how to test the possible use of denial in individuals exhibiting low death anxiety. Lewis, Espe-Pfeifer, andBlair (1999-2000) pointed out the difficulty in establishing meaning of a low death anxiety score if indeed the coping mechanism of denial is present. "The person keeps emotionally threatening thoughts and feelings from consciousness" (p. 423).…”
mentioning
confidence: 99%
“…Although Lang (1997) and Thorson and Powell (1996) found higher than average death anxiety in funeral directors, other researchers found average levels or no difference to lower levels of death anxiety between members of this population and others (Keith, 1996(Keith, , 1998Lattanner & Hayslip, 1984;Lewis, Espe-Pfeifer, & Blair, 2000;Lonetto & Templer, 1986;Rockwell, 1981;Schell & Zinger, 1984;Templer, Ruff, & Ayers, 1976). For example, Schell and Zinger assessed death anxiety levels between Canadian funeral directors (n = 149) and a group of part-time college students (n = 93) and college students majoring in computer (n = 42) and mortuary science (n = 56).…”
Section: Death Anxiety and Exposure To Deathmentioning
confidence: 79%
“…A general review of health-care professionals and comfort with end-of-life issues found studies conducted with nursing students and nurses (Allchin, 2006;Beck, 1997;Deffner & Bell, 2005;Demmer, 2000;Lewis, Espe-Pfeifer, & Blair, 1999;Payne, Dean, & Kalus, 1998;Servaty, Krejci, & Hayslip, 1996), as well as medical students and physicians (Kvale, Berg, Groff, & Lange, 1999;Lloyd-Williams & Dogra, 2003;Servaty et al, 1996;Williams, Wilson, & Olsen, 2005). In one qualitative study (Allchin), interviews with nursing students revealed care themes that included an initial hesitancy and discomfort in end-of-life situations, a need for emotionally processing the experience of providing care to the dying, and an eventual sense of personal and professional benefit from this work.…”
Section: Nursing and Medicine And End-of-life Carementioning
confidence: 99%